2002
DOI: 10.1016/s0048-9697(02)00027-x
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical evidence for atmospheric pollution derived from prehistoric copper mining at Copa Hill, Cwmystwyth, mid-Wales, UK

Abstract: This paper presents geochemical data from a blanket peat located close to a Bronze Age copper mine on the northern slopes of the Ystwyth valley, Ceredigion, mid-Wales, UK. The research objective was to explore the possibility that the peat contained a geochemical record of the pollution generateD by mining activity. Four peat monoliths were extracted from the blanket peat to reconstruct the pollution history of the prehistoric mine. Three different geochemical measurement techniques were employed and four copp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 36 publications
(30 reference statements)
7
60
0
Order By: Relevance
“…Numerous studies have concluded that ombrotrophic bogs are probably the best continental Pb archive since these ecosystems only receive Pb from the atmosphere (e.g., Shotyk et al, 1998;Weiss et al, 2002;Mighall et al, 2002). Lead is by far the most intensively studied heavy metal in peat mainly because it is considered by most authors to be immobile in ombrotrophic peat.…”
Section: Mobility Of Heavy Metals In Peat -A Short Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have concluded that ombrotrophic bogs are probably the best continental Pb archive since these ecosystems only receive Pb from the atmosphere (e.g., Shotyk et al, 1998;Weiss et al, 2002;Mighall et al, 2002). Lead is by far the most intensively studied heavy metal in peat mainly because it is considered by most authors to be immobile in ombrotrophic peat.…”
Section: Mobility Of Heavy Metals In Peat -A Short Reviewmentioning
confidence: 99%
“…Numerous studies have demonstrated the potential of ombrotrophic bogs to record past anthropogenic activities (e.g., Le Roux et al, 2004;Shotyk et al, 2003 ;Weiss et al, 2002 ;Mighall et al, 2002 ;Brännvall et al, 1999). However, studies dealing with peat inorganic geochemistry in Eastern European countries are scarce (e.g., Fialkiewicz et al 2008;Syrovetnik et al, 2007 ;Mihaljevič et al, 2006;Novak et al, 2003 ;Vile et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Shotyk et al, 1996Shotyk et al, , 2003Weiss et al, 2002;Martinez-Cortizas et al, 2002;West et al, 1997;Mighall et al, 2002;Novak et al, 2003;Le Roux et al, 2004). Most importantly, peat is particularly effective at preserving atmospheric metal deposition in the form of lead (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, peat is particularly effective at preserving atmospheric metal deposition in the form of lead (e.g. Shotyk, 2002;Shotyk et al, 1998Shotyk et al, , 2003Vile et al, 1999;Weiss et al, 1999), copper (Rausch et al, 2005;Mighall et al, 2002), nickel (Krachler et al, 2003) and zinc (Rausch et al, 2005;Twardowska et al, 1999). Recent research has shown that ancient Pb contamination in peat can be traced by Pb isotopes and fingerprinted to a local or regional origin (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This is principally due to possible mobilization of elements linked to the fluctuation of watertable, or leaching by groundwater 7,8 . However other authors [9][10][11][12][13] have demonstrated the potential of mineralotrophic peat to record past climatic or anthropogenic changes.…”
Section: Introductionmentioning
confidence: 99%